SAT-430 Quality of Life After Thyroidectomy for Patients with Hashimoto’s Disease and Persistent Symptoms - Thatipamala, Priyanka (J Endocr Soc, 2020)
Objective: To determine whether thyroidectomy improves quality of life in patients with Hashimoto’s thyroiditis with persistent symptoms despite biochemical euthyroidism. Study Design: A retrospective cohort study of patients undergoing thyroidectomy for Hashimoto’s thyroiditis. Setting: Tertiary referral center. Subjects and Methods: Included patients underwent thyroidectomy for Hashimoto’s thyroiditis at our institution between 2014 and 2018. The following variables were collected: age, race, body mass index (BMI), pre-operative symptoms, pre-operative thyroid peroxidase antibody (TPO Ab), thyroglobulin antibody (Tg Ab) thyroid stimulating hormone (TSH), free T4, specimen weight, and presence of thyroiditis or malignancy on the pathology report. The primary outcome was general health score on the Short Form-36 Health Survey (SF-36) ranging from 3–35 months postoperatively. Secondary outcomes included an additional questionnaire specifically addressing disease management after surgery as well as any adverse outcomes. Results: 19 patients were included in the study. 18 of the 19 patients were female with a mean age of 48 years (SD 13.6 years). The majority of patients were Caucasian. There was no significant difference between the general health score of the Hashimoto’s thyroiditis patients post-operatively compared to a healthy control population. (66.9 vs. 74.1; 95% CI [-16.9 + 2.5], p = 0.16). There were also no significant differences between groups within the 7 SF-36 subscores. Elevation in pre-operative TPO Ab correlated with lower reported post-operative energy levels (r = -0.63, p = 0.016) and emotional well-being (r = -.55, p = 0.041). 87.5% (14/16) of respondents reported to be moderately or extremely happy with their decision to proceed with surgery. Conclusions: Quality of life in patients with Hashimoto’s thyroiditis who undergo thyroidectomy is equivalent to the general population, and the majority of patients are satisfied with the decision to have undergone surgery. Thyroidectomy is a consideration for patients with Hashimoto’s disease and persistent symptoms despite optimization on medical therapy.